Minimum standards of clinical practice for physiotherapists working in adult intensive care units in Singapore - Bernice X Lee; Joyce C Tiew; Jovan G Lim; Diana Sani; Clement C Yan; Shane Patman; Melissa Y Chan; Meredith T Yeung (Proceedings of Singapore Healthcare, 2022)
Background Physiotherapists play a crucial role in rehabilitating critically ill patients in intensive care units (ICU). However, variations are found in clinical practice amongst physiotherapists working in the ICU, both locally and internationally, due to the lack of minimum clinical standards and varying knowledge on critical care rehabilitation resulting in inconsistent quality of care. Purpose To establish a framework of the minimum standards of clinical practice for physiotherapists working in ICU in Singapore and compare the standards with existing literature. Methods A three-round modified Delphi questionnaire survey technique collated responses from ICU physiotherapists. The questionnaire contained 222 items, categorised into assessments, conditions and treatments. Responses to the items were either: “Yes, it is essential”, “No, it is not essential”, or “I am not sure”. Consensus for an item was reached when 70% of participants ranked it essential or non-essential. Participants comprised registered physiotherapists who have worked in the ICU for at least six months in the last 12 months and are currently working in the ICU. Results 23 physiotherapists (median ICU-experience 7.0 (4.3–9.8) years) gave consent and completed the initial survey. 13 completed all three rounds of questionnaires. Overall, 163 items were regarded as essential, 21 as non-essential, and 38 did not reach consensus. The identified 163 items varied from similar studies due to different scopes of physiotherapy practice and professional autonomy. Conclusion This framework may guide the content of the physiotherapy education curriculum on critical care rehabilitation and minimise variability in clinical practice across different healthcare institutions in Singapore.